Comparison of the various pretreatment methods on Orhaneli lignite fuel characteristic - Gulen, Jale; Ozturk, Abdullah Bilal (TAYLOR & FRANCIS INC, 2025)
Lignite, with a moderate heating value, is known as one of the important energy sources due to its abundance and accessibility in many regions. However, sulfur and moisture content can restrict its environmental compatibility and heating efficiency. Therefore, improving the quality of lignite desulfurization and reducing the moisture content through microwave pretreatment to enhance its fuel characteristics is crucial for both thermal efficiency and environmental concerns. To this end, in this study, lignite samples from the Orhaneli district of Turkey were treated with chemicals, including methanol and acetic acid, following hydrogen peroxide oxidation to improve fuel characteristics and evaluate the potential impact on facilitating sulfur removal. The obtained results were comprehensively discussed. Additionally, lignite was tested under the effects of microwaves and ultrasonic waves. Furthermore, Fourier Transform Infrared (FTIR) and X-ray spectra were identified in detail.
Keywords: Lignite; pretreatment; desulfurization; fuel; characterization; ULTRA-CLEAN-COAL; 2 TURKISH LIGNITES; MINERAL MATTER; DEMINERALIZATION; REMOVAL; SULFUR; FLOTATION; Energy & Fuels; Mining & Mineral Processing